Intraoperatively Diagnosed Tracheal Tear after Using an NIM EMG ETT with Previously Undiagnosed Tracheomalacia - Minal Joshi; Simon Mardakh; Joel Yarmush; H. Kamath; Joseph Schianodicola; Ernesto Mendoza (Case Reports in Anesthesiology)
Tracheal rupture is a rare complication of endotracheal intubation. We present a case of tracheal rupture that was diagnosed intraoperatively after the use of an NIM EMG endotracheal tube. A 66-year-old female with a recurrent multinodular goiter was scheduled for total thyroidectomy. Induction of anesthesia was uncomplicated. Intubation was atraumatic using a 6 mm NIM EMG endotracheal tube (ETT). Approximately 90 minutes into the surgery, a tracheal tear was suspected. After confirming the diagnosis, conservative treatment with antibiotic coverage was favored. The patient made a full recovery with no complications. Diagnosis of the tracheal tear was made intraoperatively, prompting early management.